2006
DOI: 10.1073/pnas.0510291103
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation and genetic covariance in adult hippocampal neurogenesis

Abstract: Adult hippocampal neurogenesis is highly variable and heritable among laboratory strains of mice. Adult neurogenesis is also remarkably plastic and can be modulated by environment and activity. Here, we provide a systematic quantitative analysis of adult hippocampal neurogenesis in two large genetic reference panels of recombinant inbred strains (BXD and AXB͞BXA, n ‫؍‬ 52 strains). We combined data on variation in neurogenesis with a new transcriptome database to extract a set of 190 genes with expression patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
162
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 179 publications
(180 citation statements)
references
References 45 publications
18
162
0
Order By: Relevance
“…In the present study, A/J mice exhibited higher baseline new neuron formation than DBA/2J mice, a finding in agreement with previous reports (Kempermann and Gage, 2002;Kempermann et al, 2006). Although it is possible that A/J mice failed to show an increase in hippocampal cell proliferation in response to fluoxetine because of a ceiling effect (eg baseline proliferation is already at maximum), this is an unlikely interpretation: C57BL/6J (B6) mice have been shown to have a higher rate of hippocampal cell proliferation than A/J mice, but, unlike A/J, B6 mice are behaviorally responsive to the antidepressant effects of fluoxetine treatment (Kempermann et al, 1997(Kempermann et al, , 2006Bai et al, 2001;Hayes and Nowakowski, 2002).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…In the present study, A/J mice exhibited higher baseline new neuron formation than DBA/2J mice, a finding in agreement with previous reports (Kempermann and Gage, 2002;Kempermann et al, 2006). Although it is possible that A/J mice failed to show an increase in hippocampal cell proliferation in response to fluoxetine because of a ceiling effect (eg baseline proliferation is already at maximum), this is an unlikely interpretation: C57BL/6J (B6) mice have been shown to have a higher rate of hippocampal cell proliferation than A/J mice, but, unlike A/J, B6 mice are behaviorally responsive to the antidepressant effects of fluoxetine treatment (Kempermann et al, 1997(Kempermann et al, , 2006Bai et al, 2001;Hayes and Nowakowski, 2002).…”
Section: Discussionsupporting
confidence: 94%
“…The difference between DBA/2J and A/J is similar to that observed in previous studies, which have shown that A/J mice exhibit a higher rate of hippocampal cell proliferation than DBA/2J mice (Kempermann et al, 2006). In two strains, DBA/2J and 129S1, chronic fluoxetine treatment increased the number of BrdU-positive cells (p ¼ 0.016 and 0.02, respectively).…”
Section: Association Between Antidepressant Efficacy and Hippocampal supporting
confidence: 89%
See 3 more Smart Citations